Design and Implementation of Entrepreneurial Management in Forming Student Entrepreneurship - Munawaroh, Lum’atul; Subakri, Subakri; Turmudi, Imam; Abidin, Zainal (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2025)
The characteristics and background of students cannot be generalized from one to another. This requires good management so that it can create innovation in entrepreneurship. This study aims to analyze the design and implementation of entrepreneurship carried out in an effort to foster the entrepreneurial spirit of students. This research uses a qualitative approach with a case study research type. Data sources were obtained from five informants consisting of one Islamic Boarding School coach, one head of the Islamic Boarding School, one head of the Cooperative, one person in charge of the Business unit and one student. Research data were collected through observation, interview and documentation techniques. Data validity techniques were carried out using member checks and source triangulation and technique triangulation. The data analysis technique uses the theory of Miles Huberman and Saldana which includes data collection, data condensation, data presentation and verification or conclusion drawing. The results obtained from the research are the design and implementation of entrepreneurship management in shaping student entrepreneurship. This research is expected to be a positive contribution, provide views, and new initiatives regarding entrepreneurship management in fostering the spirit of entrepreneurship in the boarding school environment so that it can expand and provide benefits to entrepreneurship activists, especially those who are in the boarding school.